Implementasi Sistem Mobile Learning pada MI Taufiqul Athfal Bogor - Andi Prastomo (Teknik Informatika Universitas Pamulang, 2020)
The application of technology in education is being developed very intensively today, especially the use of technology to support the teaching and learning process. The transfer of conventional learning methods such as face-to-face in the classroom towards a modern direction such as distance learning using computer-based systems or smartphones (Mobile Learning) has become a common thing implemented in today's education world. But not all educational institutions implement the same thing as MI Taufiqul Athfal Bogor. The purpose of this study was to design and implement a distance learning system based on android with smartphone media (Mobile Learning) to help MI Taufiqul Athfal Bogor in the teaching and learning process. The research method used is the Research & Development (R&D) method. System testing was carried out using the ISO 9126 method by distributing questionnaires to 20 respondents who were teachers at MI Taufiqul Athfal. The test results with four aspects of ISO 9126, namely aspects of Fuctionality, Reliability, Usability, and Efficiency produce an overall Actual Total score, namely Total% Actual of 90%, thus concluding that the quality of the system is Very Good to implement. The final result of this research is an Andiroid-based Mobile Learning system designed by researchers which is implemented very well at MI Taufiqul Athfal and helps support the distance teaching and learning process.